Metadata and semantics for digital libraries and information centres - Raitt, David (The Electronic Library, 2007)
In 2005, a group of scholars decided to start a conference series related to metadata as a concrete research and inquiry discipline, called MTSR (Metadata and Semantics Research conference). The first conference took place completely online in 2005, and the second is being organized as a hybrid (part physical, part on-line) event by the Ionian Academy of Corfu (Ionian University) that will take place in 2007. The conference aims at bringing together researchers and practitioners that share a common interest in metadata, its representation, its semantics and its diverse applications. The conten
Keywords: Metadata; Management information systems